Answer:
Therefore, the standard for will be:
![y=(1)/(4)x^(2)-x-4](https://img.qammunity.org/2022/formulas/mathematics/college/pwt3e6qfa3iiqf6fshlbuphnlbl0tcth78.png)
Explanation:
The equation of a parabola written as vertical axes is given by:
(1)
The vertex of the parabola (h,k) is (2,-5).
The focus (h,k+p) is (2,-4)
Then we can find p knowing that:
h = 2
k = -5
k + p = -4 then p = -4+5 = 1
Putting all these values in equation (1) we will find the equation of the parabola:
![(x-2)^(2)=4(1)(y-(-5))](https://img.qammunity.org/2022/formulas/mathematics/college/ix2un0i3th8fzm9f8kmnbelcazw892ud8d.png)
(2)
Now, we need to find the standard form of the equation of the parabola.
Let's recall that standard form is:
We just need to work out equation (2) to convert it to the standard form.
![(x-2)^(2)=4(y+5)](https://img.qammunity.org/2022/formulas/mathematics/college/usl42lb0cfe5vlmr995v6cl0cbqvrvsrl4.png)
![x^(2)-4x+4=4(y+5)](https://img.qammunity.org/2022/formulas/mathematics/college/aa8ey2q9v6qy67gxq0qf4xbxzb9k89ou7x.png)
![(1)/(4)x^(2)-x+1=y+5](https://img.qammunity.org/2022/formulas/mathematics/college/twosivrgg0wzy9ynoyhl465xeupew3zoc7.png)
Therefore, the standard for will be:
![y=(1)/(4)x^(2)-x-4](https://img.qammunity.org/2022/formulas/mathematics/college/pwt3e6qfa3iiqf6fshlbuphnlbl0tcth78.png)
I hope it helps you!